Review of Genetic Variants of Butyrylcholinesterase and Their Potential Impact on Human Health - Nugraha, Bharmatisna Anggaharsya (Open Access Indonesian Journal of Medical Reviews, 2021)
Butyrylcholinesterase (BChE) is an enzyme found in plasma and many other parts of the body. It is enzyme that hydrolyses drugs containing ester bonds such as drugs acting at the neuromuscular junction (succinylcholine) and local anaesthetics (procaine). Examination of the gene for mutations or polymorphisms causing the observed biochemical phenotypes has isolated those responsible for all the most widely known variants. The molecular bases of several genetic variants of BChE have been reported, such as the Atypical variant, fluoride-resistant variant, silent variant, K variant, J variant and C5 variant. In general, BChE polymorphisms have been shown to produce enzymes with varying levels of catalytic activity. Genetic variants of human butyrylcholinesterase were one of the first examples in the new field of pharmacogenetics when it was recognized that abnormal response to the succinylcholine was due to a mutated enzyme with low binding affinity. Beside that, variant of BChE has potential impact for Alzheimer disease patology.